Demographic Changes and Economic Growth of Sub-Sahara Africa: A System GMM Approach - Akpansung, Aniekan O.; Peter, Amade (NIU Journal of Social Sciences, 2021)
Empirical evidences show that the relationship between demographic dynamics and economic growth is mixed and controversial. This study investigates the impact of demographic changes on economic growth of sub-Sahara African (SSA) countries using annual data between 1980 and 2019. The results based on System Generalized Method of Moments (SGMM) estimation technique revealed that urbanization rate and aging-population (65 + years) have positive and significant impact on economic growth of SSA countries, while unemployment rate exerts a significant negative impact. The study concludes that urbanization is very significant in reducing unemployment in the rural areas and promoting economic growth, therefore its importance should not be exaggerated. The study recommends that SSA countries should put urbanization at the heart of their socio-economic policies and programmes so that it can extend economic opportunities and potentials to the rural areas, which will serve as impetus for rapid economic growth of the SSA countries. Keywords: Demographic change, Economic growth, SGMM, Sub-Sahara Africa